Can the application of multi-mode adhesive be a substitute to silicatized/silanized Y-TZP ceramics? - de Araújo, Arthur Magno Medeiros; Januário, Ana Beatriz do Nascimento; Moura, Dayanne Monielle Duarte; Tribst, João Paulo Mendes [UNESP]; Özcan, Mutlu; E Souza, Rodrigo Othávio de Assunção (My University, 2018)
This study evaluated the effectiveness of a multi-mode adhesive (SBU-Scotch Bond Universal/3M) as a substitute for silica coating and silane application on the bonding of zirconia ceramics to resin cement. One-hundred and twenty sintered zirconia ceramic blocks (5 × 5 × 5 mm) were obtained, finished by grounding with silicon carbide paper (#600, #800, #1000 and #1200) and randomly divided into 12 groups (n=10) in accordance with the factors “surface treatment” (ScSi-silicatization + silanization; ScSBU-silicatization + SBU; SBU-SBU without photoactivation and SBUp-SBU photoactivated) and “ceramic” (Lava/ 3M ESPE, Ceramill Zirconia/ Amann Girrbach and Zirkonzahn/ Zirkonzahn). Dual resin cement cylinders (RelyX Ultimate/3M ESPE) were subsequently produced in the center of each block using a silicon matrix (Ø=2 mm, h=5 mm) and photoactivated for 40 s (1200 mW/cm2). The samples were stored for 30 days in distilled water (37ºC) and submitted to shear bond strength test (1 mm/min, 100 KgF). Data (MPa) were analyzed under ANOVA (2 levels) and Tukey test (5%). Complementary analyzes were also performed. ANOVA revealed that only the factor “surface treatment” was significant (p=0.0001). The ScSi treatment (14.28A) promoted statistically higher bond strength values than the other ScSBU (9.03B), SBU (8.47B) and SBUp (7.82B), which were similar to each other (Tukey). Failure analysis revealed that 100% of the failures were mixed. The silica coating followed by the silanization promoted higher bond strength values of resin cement and ceramic, regardless of the zirconia ceramic or SBU.
Keywords: Bond strength; MDP primer; Silica coating; Surface treatment; Zirconia